A oralidade nas aulas de língua portuguesa : a produção do gênero debate - Barros, José Batista de (2014)
This research aims at analyzing the uses of orality within L1 basic cycle portuguese classes in the pedagogical scenario of public debate as a curricular component. The epistemic corollaries which pinpoint that research are based upon theoretical perspectives whose intersection is language enunciation studies, that is to say, Bakhtin/Volochinov (2002) propositions on language interactional philosophy. Bakhtin´s discourse genre theory (2003) outlined within communicative interaction dialogism, as much as the associated premisses under the orality and literacy plateau according to the social-interactionism model presented by Marcuschi (2001, 2002, 2003, 2004, 2008) and Dolz & Schneuwly (2011) in terms of oral and written text genre didactics in regular school. The supracited analysis is predominantly qualitative and consisted of four debates tasks in Portuguese classes at Colégio de Aplicação da UFPE school in an 8th grade group. The investigation corpora is composed by questionnaire surveys applied with students and teachers, class observation diaries, photographs and debate audios, as well as diverse resources used by the participants. The results outline a better understanding of orality usage in school based on the debate theoretical study: a) teacher and students comprehend the social and discourse functions of such genre under the scope of verbal language interactive practices; b) teaching sequencing with the public debate emphasizes the theme selection, rule and role orientations; c) talking management, with the organization and turn distribution was a special role for facilitators, thus contributing to a better comprehensible speaking and listening. d) In speaking-writing articulation, the retextualization of oral and written genres sharpened the argumentation process. As for the cited discourse, it has been observed as an intertextual mechanism to achieve genre relations and, above all, to favor argument negotiations as debaters´ speech were re-cited as agreeing/disagreeing manners.